2021
DOI: 10.1002/app.51682
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced positive temperature coefficient effect by crosslinking reaction for silicone rubber/carbon black composites with high pressure sensitivity

Abstract: Positive temperature coefficient (PTC) composites are usually made of crystalline plastics and conductive fillers, but they are not suitable for flexible electronic devices because of their high rigidity. Rubber-based PTC composites are flexible but their PTC intensity is low. In this work, based on the effect of crosslinking reaction on the electrical conductivity of silicone rubber composites, silicone rubber/conductive carbon black composites with an obvious PTC effect were prepared. Compared with the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…To synthesize uniform CB/SR conductive composites, the key challenge is to overcome the agglomerate behavior of CB particles within silicone rubber matrices. One of the promising approaches is the optimized mixing method with various mechanical stirring or/and chemical modifications. Representatively, Kong et al fabricated homogeneous CB/PDMS nanocomposites through this method, as shown in Figure a. The CB particles could be well dispersed in the PDMS matrix by using toluene as the solvent of CB particles and PDMS, accompanied by mechanical vibration, i.e., the ultrasonication of individual CB particles/toluene and PDMS/toluene and the magnetic stirring of CB/PDMS/toluene.…”
Section: Silicone Rubber Based-conductive Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…To synthesize uniform CB/SR conductive composites, the key challenge is to overcome the agglomerate behavior of CB particles within silicone rubber matrices. One of the promising approaches is the optimized mixing method with various mechanical stirring or/and chemical modifications. Representatively, Kong et al fabricated homogeneous CB/PDMS nanocomposites through this method, as shown in Figure a. The CB particles could be well dispersed in the PDMS matrix by using toluene as the solvent of CB particles and PDMS, accompanied by mechanical vibration, i.e., the ultrasonication of individual CB particles/toluene and PDMS/toluene and the magnetic stirring of CB/PDMS/toluene.…”
Section: Silicone Rubber Based-conductive Compositesmentioning
confidence: 99%
“…Moreover, a time-stable resistance (less than 1% change over more than 8 months) and a low stiffening impact on the elastomer have been proven. Besides, an in situ formation method has also been used to form 0D metallic nanomaterial-based silicone rubber-based conductive composites. ,, On the basis of this method, Park et al developed AgNP/SEBS conductive composites, which could maintain a conductivity of ∼2200 S/cm at 100% strain.…”
Section: Silicone Rubber Based-conductive Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…High-density polyethylene (HDPE) is a typical semicrystalline polymer, commonly used as a matrix for PTC materials. , In CB-loaded HDPE nanocomposites, strong NTC effects are occasionally observed above the PTC transition, when a new network is formed by the thermally induced motion of the conducting particles in the matrix. In order to limit these undesirable effects, various methods have been proposed to eliminate the NTC behaviors of the nanocomposites. One of the methods for controlling the NTC behaviors is to increase the crosslinking of the HDPE matrix and thus limiting the mobility of CBs inside the matrix. , …”
Section: Introductionmentioning
confidence: 99%
“…31−33 One of the methods for controlling the NTC behaviors is to increase the crosslinking of the HDPE matrix and thus limiting the mobility of CBs inside the matrix. 34,35 Since electron beam (EB) irradiation technology has been developed for a variety of plastic applications, such as cable sheaths, formed plastics, the radial tire industry, and so forth. 36,37 The main advantage of this technology is that it can alter the inherent chemical, structural, physical, and thermal properties of polymers, thereby providing lower cost and higher product purity.…”
Section: Introductionmentioning
confidence: 99%